Evaluation of Tolerance Character of Elementary School Students Based on Gender Through Network Analysis: Efforts to Strengthen Responsive Character Education - Hijrawatil Aswat; Abdul Manaf; Nurmin Aminu; Anisa Rizkayati; Ali Yusril Dati; Septi Nurbaiti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to evaluate the character values of tolerance of elementary school students based on gender, as well as formulate strategies to strengthen responsive character education. This study uses a quantitative approach with an exploratory descriptive survey design. The sample consisted of 688 students, 72 students were used for instrument quality testing and 616 students for tolerance character value analysis. First, the test results of the instrument with the Rasch model show high reliability of people and items. Second, the descriptive analysis showed that the tolerance levels of male and female students were relatively balanced, with significant differences only in the higher aspect of respect for other people's peers in female students. Third, network analysis revealed that male students' tolerance values were centered around dominant nodes (key indicators), whereas female students formed a more evenly distributed and interconnected value network. Fourth, the implications of these findings highlight the importance of character education strategies that are data-driven, differentiated, and contextual. These strategies are directed at teachers to strengthen classroom instruction by focusing on reinforcing weaker tolerance indicators, at curriculum developers to integrate tolerance values into cross-theme lessons, and at policymakers to design gender responsive training programs.